Monitoring Gear for Environment Chamber - Dietrich, T. A. (1965)
An unidentified man wearing a vest containing sensory equipment, standing beside monitoring gear for environmental chamber. Per the label on the vest, the equipment was fabricated for a NASA contract, NAS 9-3910, which involved the development of monitoring and safety equipment for use in the extreme conditions of a space simulation chamber. The vest contained much of the instrumentation; carbon dioxide and oxygen sensors were housed in an unpictured helmet.
Keywords: Scientific apparatus and instruments; Atmosphere--Analysis; Atmospheric carbon dioxide--Measurement; Electronics in space medicine; Beckman Instruments, Inc.; Oxygen--Measurement